Green Mosque: A Living Nexus - Omar, Siti Syamimi; Ilias, Nur Hanim; Teh, Mohd Zulhaili; Borhan, Ruwaidah (Environment-Behaviour Proceedings Journal, 2018)
Traditionally, mosques, especially in the Middle East perform more functions than just being a place of worship. A mosque is also a place to generate economy, education and social cohesion of the community. In this paper, it is aimed to explore the potential of a green mosque in a small newly developed neighbourhood which is Masjid as-Siddiq in the State of Perak as a case study to become a living nexus by focusing on three main aspects of sustainability which are environmental, social and economic. Lastly, new recommendations will be suggested for Masjid as-Siddiq to become a greener mosque.